2014
DOI: 10.1380/ejssnt.2014.97
|View full text |Cite
|
Sign up to set email alerts
|

Dot-Like Formation of Metal Nanocrystals from Exfoliated Ruthenate Nanosheets

Abstract: We studied the metallization behavior of molecularly thin Ru0.95O 0.2− 2 nanosheets obtained from complete delamination of a layered ruthenate, K0.2RuO2.1. Heating at 200• C under a mixture of N2 and H2 transformed multilayers of the nanosheets into hcp-Ru metals. These metals have unique morphology reflecting the multilayer structure of the precursors. Interestingly, a monolayer state of the Ru0.95Onanosheets triggered a dot-like formation of Ru metal nanocrystals about 0.6 nm thick and several tens of nanome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…S4). Based on these data and our previous work, 24 it is concluded that H 2 treatment of RuO 2.1 ns-PtRu/C at 200…”
Section: Resultssupporting
confidence: 78%
“…S4). Based on these data and our previous work, 24 it is concluded that H 2 treatment of RuO 2.1 ns-PtRu/C at 200…”
Section: Resultssupporting
confidence: 78%
“…RuO 2 nanosheets can be reduced to metallic 2D monolayer Ru nanosheets by hydrogen treatment. 58,59 Figure 13 (Fig. 13(b)), it is concluded that H 2 treatment of RuO 2 nanosheets at moderate temperatures results in topotactic reduction to metallic Ru nanosheets.…”
Section: Ru Core@pt Shell Nanosheets For Pt-based Fuel Cell Electrocamentioning
confidence: 92%
“…In the past decade, the primitive structural conversion of exfoliated nanosheets has demonstrated significant potential in the design of 2D materials; for example, the exfoliated nanosheets of the TiO 2 system in the monolayer state transformed into platelike TiO 2 anatase nanocrystallites upon heating to temperatures above 800 °C. , Moreover, it is well-known that the structural conversion of chalcogenide nanosheets such as MoS 2 produces several polymorphs with different properties. In contrast to these structural conversions in binary systems, reduction of graphite oxide nanosheets into graphene without disruption of the sheet-structure can be depicted as a simplification of the material composition from a C–O binary system to a C monocomponent system . More recently, we have succeeded in producing unusual metal nanosheets via a similar topotactic reduction of oxide nanosheets, , indicating that a binary transition metal oxide system can be simplified in only transition metal elements. Thus, structural conversions using the exfoliated nanosheets are known to be mainly attained in the same composition system or a simpler composition system.…”
Section: Introductionmentioning
confidence: 99%
“…19−22 In contrast to these structural conversions in binary systems, reduction of graphite oxide nanosheets into graphene without disruption of the sheetstructure can be depicted as a simplification of the material composition from a C−O binary system to a C monocomponent system. 14 More recently, we have succeeded in producing unusual metal nanosheets via a similar topotactic reduction of oxide nanosheets, 23,24 indicating that a binary transition metal oxide system can be simplified in only transition metal elements. Thus, structural conversions using the exfoliated nanosheets are known to be mainly attained in the same composition system or a simpler composition system.…”
Section: ■ Introductionmentioning
confidence: 99%